Critical Role of Tumor Microenvironment in Shaping NK Cell Functions: Implication of Hypoxic Stress - Hasmim, Meriem; Messai, Yosra; Ziani, Linda; Thiery, Jerome; Bouhris, Jean-Henri; Noman, Muhammad Zaeem; Chouaib, Salem (Frontiers in Immunology, 2015)
Blurring the boundary between innate and adaptive immune system, natural killer (NK) cells, a key component of the innate immunity, are recognized as potent anti-cancer mediators. Extensive studies have been detailed on how NK cells get activated and recognize cancer cells. In contrast, few studies have been focused on how tumor microenvironment-mediated immunosubversion and immunoselection of tumor resistant variants may impair NK cell function. Accumulating evidences indicate that several cell subsets (macrophages, myeloid-derived suppressive cells, T regulatory cells, dendritic cells, cancer-associated fibroblasts, and tumor cells), their secreted factors as well as metabolic components (i.e. hypoxia) have immunosuppressive roles in the tumor microenvironment and are able to condition NK cells to become anergic. In this review, we will describe how NK cells react with different stromal cells in the tumor microenvironment. This will be followed by a discussion on the role of hypoxic stress in the regulation of NK functions. The aim of this review is to provide a better understanding of how the tumor microenvironment impairs NK functions, thereby limiting the use of NK cell-based therapy, and we will attempt to suggest more efficient tools to establish a more favorable tumor microenvironment to boost NK cytotoxicity and control tumor progression.